IMPLEMENTATION OF DEVOPS APPROACH USING CI/CD WITH A SHARED-PIPELINE TO ACCELERATE WEB SERVICE DEVELOPMENT - Ahmad Lukman Hakim; Diah Aryani; Daniati Uki Eka Saputri (LPPM Nusa Mandiri, 2026)
The development of microservices-based web service applications requires fast, consistent, and automated integration and deployment processes. However, in practice, many organizations still rely on manual procedures and non-standardized pipeline configurations, which lead to release delays and increase the risk of operational errors. The DevOps approach through Continuous Integration and Continuous Delivery (CI/CD) has emerged as a relevant solution. Nevertheless, its practical implementation still requires clear and reusable guidance. This study aims to implement DevOps approach using CI/CD practices for the backend microservices at JEL Tech Inc by leveraging GitLab and a shared-pipeline scheme. The research adopts an applied research methodology with a case study approach, following the stages of the DevOps lifecycle, including plan, code, build, test, release, deploy, operate, and monitor. Pipeline automation is constructed using modular shell scripts executed by GitLab Runner and integrated with Docker, a Container Registry, and Kubernetes. The results demonstrate that the implementation of a shared-pipeline successfully standardizes build, package, and deployment processes across multiple microservices repositories. The implementation results show measurable improvements, including up to 90% reduction in deployment time, 400% increase in release frequency, and significant reduction in failure rates. This study contributes a reusable shared-pipeline architecture that extends existing DevOps implementation practices by providing a standardized, modular, and testable CI/CD model for microservices environments.